PENGARUH MODEL COOPERATIVE LEARNING TIPE JIGSAW BERBANTUAN MEDIA SCRAPBOOK TERHADAP KETERAMPILAN BERBICARA PESERTA DIDIK DI SEKOLAH DASAR - Mohamad Fikri Maulana; Dindin M.Z.M; Feby Inggriyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background of this study is the difficulty in improving speaking skills, the average value of students' speaking skills at SDN Cileunyi 3 in learning under the KKM, because there are students who lack confidence when speaking, learning tools are not maximal when teaching, delivering material by lecturing , learning is focused on educators, therefore when the learning process of students tends to become monotonous. Based on this, it is necessary to have a learning model so that students must interact more with their friends and teachers in learning so that they become accustomed to speaking and communicating. The purpose of this study was to determine the effect of the Jigsaw Cooperative Learning learning model. The method used in this study is a quasi-experimental quasi-experimental research method. The design used is the control group design. Data collection techniques through tests, observation, and documentation. The tests used used the pretest and posttest which were used as data on students' speaking skills. The sample used was class IV-A as the experimental class using the Jigsaw Cooperative Learning model and class IV-B as the control class using the Conventional model. Data processing techniques were carried out using the normality test, homogeneity test, independent sample t test, NGain test and effect size test assisted by IBM SPSS Statistic 25 software. Based on the research results, an overview of the learning process was obtained using the Jigsaw Cooperative Learning Type assisted learning model. media scrapbook. There is a big influence on the use of the Jigsaw Cooperative Learning learning model with a value of 1.8 in the effect size test and a significant value of 0.000 through the Independent Sample T-Test.